Keberhasilan Okulasi Jati (Tectona grandis L.f.) Hasil Eksplorasi di Gunung Kidul - Sapto Indrioko; Eny Faridah; Aan Yuli Widhianto (Jurnal Ilmu Kehutanan, 2010)
Grafting Success  Story of Teak (Tectona grandis L.f.) from Exploration Material in Gunung KidulTeak exploration as planting material source of superior genotype is necessary for hedge orchard establishment for forest communities in order to produce the planting material by themselves. The objective of this study is to identify the success and growth of teak grafting resulted from exploration in Gunung Kidul region.The exploration aimed to collect teak ortet (mother tree). The ortets would be used as materials for hedge orchard, as the cutting source for community forest plantation. The study was conducted in Gunung Kidul region (for exploration) and in the Laboratorium on Intensive Silviculture, Silviculture Department, Faculty of Forestry UGM. In the laboratory, the first three months was to examine grafting compatibility, and the second three months to monitor the growth of teak grafting. The experiment in the laboratory was performed with Completely Randomized Design (CRD), with treatment of 16 clones and 10 treeplot replication each, making total of 160 clones.The study resulted in the following: 1) from the exploration, there were 52 clones having good genotypes; 2) from the 52 good-genotype clones, there were 16 clones having good compatibility; 3) in the period of 3 months, the best height growth was shown by clone number 6 with 27 cm; the best diameter growth by clone number 5 with 0.252 cm, and in term of leaf number, the best was shown by clone number 15 with 9.2 blades. In general clone number 6 showed the best compatibility and growth, with sprout life percentage of 37.03%; height growth of 2.7 cm; diameter growth of 0.114 cm and leaf number of 9.2 blades.